2004
DOI: 10.1111/j.0269-283x.2004.00497.x
|View full text |Cite
|
Sign up to set email alerts
|

Population structure of the peridomestic mosquito Ochlerotatus notoscriptus in Australia

Abstract: Ochlerotatus notoscriptus (Skuse) (Diptera: Culicidae) is the predominant peridomestic mosquito in Australia where it is the primary vector of dog heartworm, Dirofilaria immitis (Leidy), and a potentially important vector of arboviruses (Barmah Forest, Ross River) with geographical variation of vector competence. Although widespread, Oc. notoscriptus has low dispersal ability, so it may have isolated subpopulations. The identification of gene flow barriers may assist in understanding arbovirus epidemiology and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
(37 reference statements)
1
14
1
Order By: Relevance
“…It also suggested that the genetic homogeneity was probably caused by a continuous and random gene flow, with a restrictive random gene drift, along a major part of the Colombian Atlantic coast. In contrast, other studies, such as that of Foley et al (2004), showed a clear significant spatial structure in mosquito species. They found a strong spatial structure in the peridomestic mosquito O. notoscriptus, with correlograms of different loci showing positive and significant values in the first distance classes and significant and negative values at the largest distances, reflecting isolation by distance.…”
Section: Discussioncontrasting
confidence: 61%
“…It also suggested that the genetic homogeneity was probably caused by a continuous and random gene flow, with a restrictive random gene drift, along a major part of the Colombian Atlantic coast. In contrast, other studies, such as that of Foley et al (2004), showed a clear significant spatial structure in mosquito species. They found a strong spatial structure in the peridomestic mosquito O. notoscriptus, with correlograms of different loci showing positive and significant values in the first distance classes and significant and negative values at the largest distances, reflecting isolation by distance.…”
Section: Discussioncontrasting
confidence: 61%
“…Aedes notoscriptus is the dominant species, most likely as a result of its extensive utilization of container habitats. This species is the predominant peridomestic mosquito in Australia (Foley et al, 2004), and the same pattern is being observed in northern New Zealand. Culex quinquefasciatus is the other exotic mosquito commonly found, but it appears to have a more restricted distribution (Derraik and Slaney, 2005).…”
Section: Disturbance Exotic Mammals and Mosquitoessupporting
confidence: 57%
“…In Australia, Ae. notoscriptus is the main peridomestic mosquito species (Foley et al, 2004), and this pattern is now seen in urban and suburban areas in the Auckland region (e.g., Derraik, 2005a). A similar pattern of invasion would likely apply to Ae.…”
Section: Discussionmentioning
confidence: 99%